Hydrogen Risk Assessment Studies: A Review Toward Environmental Sustainability - Mimi Min; Cheolhee Yoon; Narin Yoo; Jinseo Kim; Yeosong Yoon; Seungho Jung (Energies)
The transition to hydrogen as a clean energy source is critical for addressing climate change and supporting environmental sustainability. This review provides an accessible summary of general research trends in hydrogen risk assessment methodologies, enabling diverse stakeholders, including researchers, policymakers, and industry professionals, to gain insights into this field. By examining representative studies across theoretical, experimental, and simulation-based approaches, the review highlights prominent trends and applications within academia and industry. The key focus is on evaluating risks in stationary and transportation applications, paying particular attention to hydrogen storage systems, transportation infrastructures, and energy systems. By offering a concise yet informative summary of hydrogen risk assessment trends, this paper aims to serve as a foundational resource for fostering safer and more sustainable hydrogen systems.